Lazarus. Volume 4, Poison - Rucka, Greg (Image Comics, Inc., 2016)
The world now lies divided not amongst political or geographic boundaries but amongst financial ones. Wealth is power, and that power rests with only a handful of families. Two of those families are at war. Carlyle and Hock are battling for control of North America. Malcolm Carlyle hovers at death's door, the victim of a poison created by Jakob Hock. As his eldest son, Stephen, struggles to fill his father's shoes, Carlyle's allies are growing more nervous, fearing an imminent defeat in the strategically important city of Duluth. Forever Carlyle, the genetically-modified Lazarus of her Family, is dispatched to Duluth with one simple goal: to keep the city from falling to Hock.